2015
DOI: 10.1108/jhom-07-2014-0119
|View full text |Cite
|
Sign up to set email alerts
|

Research “push”, long term-change, and general practice

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(66 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…This finding was also reflected in the post intervention group interview with the nurses, a component of the qualitative work within the MOSAICS study [43, 44]. In a group interview the nurses described how they felt more confident dealing with patients who consulted with OA and were able to modify their relationship with OA patients, because they had the opportunity to play more of an active role in patient care [43]. Ong et al [44] also reported that the nurses recognised that they had lacked skills and knowledge of OA previously, felt that the training had helped to up skill them in this regard, and left them feeling they could manage patients with OA better than previously, and boosted their professional standing.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This finding was also reflected in the post intervention group interview with the nurses, a component of the qualitative work within the MOSAICS study [43, 44]. In a group interview the nurses described how they felt more confident dealing with patients who consulted with OA and were able to modify their relationship with OA patients, because they had the opportunity to play more of an active role in patient care [43]. Ong et al [44] also reported that the nurses recognised that they had lacked skills and knowledge of OA previously, felt that the training had helped to up skill them in this regard, and left them feeling they could manage patients with OA better than previously, and boosted their professional standing.…”
Section: Discussionmentioning
confidence: 81%
“…This seems to be reflected in the clinical management, as it appears that the nurses focused on the core treatments of information provision, encouraging weight management and physical activity. This finding was also reflected in the post intervention group interview with the nurses, a component of the qualitative work within the MOSAICS study [43, 44]. In a group interview the nurses described how they felt more confident dealing with patients who consulted with OA and were able to modify their relationship with OA patients, because they had the opportunity to play more of an active role in patient care [43].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, opportunities for reconfiguring the intervention activities-considered a subconstruct of reflexive monitoring in NPT-were important for sustainment, which is in correspondence with implementation studies using NPT (e.g., Pope, 2013) and with the wider literature on diffusion of innovations (Greenhalgh et al, 2008;Rogers, 2003 The significance of the social systems within which normalisation processes take place is also emphasised in recent theoretical developments of NPT (May et al, 2016). Similarly, in a NPT-inspired study of a complex intervention in primary care, Morden et al (2015) found the policy context to be critical for general practitioners' decisions if to continue a complex intervention after the trial ended.…”
Section: Eses First Since Scheirer's Typology Of Interventions Is Bmentioning
confidence: 78%
“…The significance of the social systems within which normalisation processes take place is also emphasised in recent theoretical developments of NPT (May et al, ). Similarly, in a NPT‐inspired study of a complex intervention in primary care, Morden et al () found the policy context to be critical for general practitioners' decisions if to continue a complex intervention after the trial ended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation